Analisis Profitabilitas Usaha Pengolahan Kalokalo di Kelurahan Wajo Kecamatan Murhum Kota Baubau (Kasus Pada Kelompok Usaha Zurqi) - Endriansyah, Rizal; La Ola, Taane; Zani, Munirwan (Department of Agribusiness, Halu Oleo University, 2018)
The analysis of the processing business profitability kalokalo in the wajo village, Murhum subdistrict in the city of bau-bau (in the case of processing kalokalo zurqi) guide by Taane La ola as a first mentor and Munirwan Zani as second mentors. This study aims to identify processing business profitability kalokalo zurqi in the wajo village, Murhum subdistrict in the city of bau-bau. This study conducted in November 2016 until August 2017. Population in this research is the head of members and members of the zurqi business group are 5Â people. Because the population is small, then the determination of the research sample is done by using the census system., so the number of research sample is 5 people. The result of the research shows that the profitability product kalokalo sugar taste in November 2016 of 52,73%, the original taste of kalokalo products can generate profits of 49,39%.